2023
DOI: 10.31234/osf.io/x5a36
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Idiopathic hypersomnia symptoms in the forms of recurrent lucid dreams and out-of-body experiences: A preliminary study

Abstract: Objective. The arousal of consciousness during REM sleep can lead to states of sleep paralysis (SP), lucid dreaming (LD), out-of-body experiences (OBEs), and false awakening (FA). We know that recurrent SP is a symptom of sleep disorders like insomnia or narcolepsy. This study hypothesizes that other recurrent phenomena related to SP could also be signs of sleep deviations like insomnia and idiopathic hypersomnia (IH). The results of the study could simplify the diagnostic process for sleep disorders in adults… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Previous research indicates that 88% of all people experience one of these phenomena at least once in their life (Raduga, Kuyava, & Sevcenko, 2020). In this study, we use the general term phase state (PS) or phase (Raduga, 2004) to refer to all states with the two characteristics of REM sleep and consciousness. Using this umbrella term allows us to observe a more complete physiological picture than would be possible while considering any single phenomenon in isolation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research indicates that 88% of all people experience one of these phenomena at least once in their life (Raduga, Kuyava, & Sevcenko, 2020). In this study, we use the general term phase state (PS) or phase (Raduga, 2004) to refer to all states with the two characteristics of REM sleep and consciousness. Using this umbrella term allows us to observe a more complete physiological picture than would be possible while considering any single phenomenon in isolation.…”
Section: Introductionmentioning
confidence: 99%
“…Several other phenomena share LD' primary features (e.g., consciousness during REM sleep), including sleep paralysis 50,51 , false awakenings 52 , and out-of-body experiences [53][54][55] . These states are grouped under the term phase state (PS) 55,56 or dissociated REM state 57 . A survey revealed that 88% of people have experienced at least one phase state; 43% of people experience one or more of them often 58 .…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of an LD induction technique can vary depending on which method is used. For example, performing techniques while falling asleep in the evening has the lowest efficiency (Raduga, 2004(Raduga, , 2014.…”
mentioning
confidence: 99%